Pengaruh Employer Branding, Reputasi Perusahaan, dan Informasi Sosial Media Terhadap Intention To Apply pada Gen Z lulusan SMK se-Bandung Raya - Azahra, Syifa Aulia; Muttaqin, Ridlwan (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
Termination of Employment (PHK), recession, and global economic growth accelerate market disruption. Companies strive to get new customers and gain greater profits than their competitors. In addition, they are very excited to attract prospective workers who have expertise in the field they are proficient in. According to the Central Statistics Agency (BPS) of Bandung City, the Open Unemployment Rate in 2023 is 8.83%. Vocational school graduates contribute the largest portion of the Gen Z unemployment rate. Thus, this research seeks to determine whether there is an influence of employer branding, company reputation, social media information on the intention to apply for a job in Gen Z. This research uses quantitative methods and data collection techniques through questionnaires and the samples used consist of 100 Gen Z respondents of vocational school graduates using cluster sampling techniques. The Likert scale is a multiple linear regression distribution and analysis used to process data. Partially employer branding has a positive effect on the intention to apply, while the company's reputation and social media information have no effect on the intention to apply.